An assessment of the impact of large goitres on perioperative and postoperative airway management: a retropsective review - Golding, Tarryn (Department of Anaesthesia, 2018)
It is widely assumed in the literature that large thyroid goitres pose a significant risk to the airway perioperatively. They are of concern to anaesthetists because of anticipated difficulty relating to intubation, ventilation and post-thyroidectomy tracheomalacia. They are of concern to surgeons because of the anticipated risk of difficult dissection and increased risk of surgical complications including haemorrhage, laryngeal nerve injury and tracheomalacia. Objectives: To analyse the folders of patients who have undergone anaesthesia and surgery for large, nonmalignant goitre, to assess the impact of large goiters on perioperative and postoperative management. An attempt will also be made to identify possible predictive markers/ patient characteristics associated with difficult intubation. Design: A retrospective folder review Setting: Groote Schuur Hospital Participants: All patients who had thyroidectomies performed at Groote Schuur Hospital between Jan 2010 and June 2016 for large, non-malignant goitres. Measurements and main results: Of the patients who underwent a thyroidectomy procedure at Groote Schuur Hospital between Jan 2010 and June 2016, 196 were identified as having non-malignant goitre and size in one dimension of greater than fifty millimeters. There were seven documented difficult intubations and only one case of failed intubation. This case was subsequently put onto cardiopulmonary bypass and intubated successfully using a rigid fibreoptic bronchoscope. Of the one hundred and nighty-six cases, four were intubated using a fibreoptic bronchoscope, eight with a videolaryngoscope, and six cases, a bougie. All other patients underwent uneventful tracheal intubation via direct laryngoscopy. All glands were removed via a collar incision with no requirement to proceed to sternotomy. There was only one patient requiring blood intraoperatively and only four reported cases of postoperative haematomas. There were no instances of tracheomalacia. Two patients suffered long term recurrent laryngeal nerve injury with voice changes. Conclusion: The data shows that, in patients with large, benign goitre undergoing thyroidectomy, airway difficulties at intubation and surgical and anaesthetic complications postextubation are rare. Intravenous induction and direct laryngoscopy is a safe technique in appropriately experienced hands.